Usual care and management of fall risk increasing drugs in older dizzy patients in Dutch general practice - Hanneke Stam; Thomas Harting; Marjolijn van der Sluijs; Rob van Marum; Henriëtte van der Horst; Johannes C. van der Wouden; Otto R. Maarsingh (Taylor & Francis Group, 2016)
Objective: For general practitioners (GPs) dizziness is a challenging condition to deal with. Data on the management of dizziness in older patients are mostly lacking. Furthermore, it is unknown whether GPs attempt to decrease Fall Risk Increasing Drugs (FRIDs) use in the management of dizziness in older patients. The aim of this study is to gain more insight into GP's management of dizziness in older patients, including FRID evaluation and adjustment. Design: Data were derived from electronic medical records, obtained over a 12-month period in 2013. Setting: Forty-six Dutch general practices. Patients: The study sample comprised of 2812 older dizzy patients of 65 years and over. Patients were identified using International Classification of Primary Care codes and free text. Main outcome measures: Usual care was categorized into wait-and-see strategy (no treatment initiated); education and advice; additional testing; medication adjustment; and referral. Results: Frequently applied treatments included a wait-and-see strategy (28.4%) and education and advice (28.0%). Additional testing was performed in 26.8%; 19.0% of the patients were referred. Of the patients 87.2% had at least one FRID prescription. During the observation period, GPs adjusted the use of one or more FRIDs for 11.7% of the patients. Conclusion: This study revealed a wide variety in management strategies for dizziness in older adults. The referral rate for dizziness was high compared to prior research. Although many older dizzy patients use at least one FRID, FRID evaluation and adjustment is scarce. We expect that more FRID adjustments may reduce dizziness and dizziness-related impairment. Key Points It is important to know how general practitioners manage dizziness in older patients in order to assess potential cues for improvement. This study revealed a wide variety in management strategies for dizziness in older patients. There was a scarcity in Fall Risk Increasing Drug (FRID) evaluation and adjustment. The referral rate for dizziness was high compared with previous research.